Annealing of Au, Ag and Au–Ag alloy nanoparticle arrays on GaAs (100) and (111)B. (26th April 2017) - Whiticar, Alexander M; Mårtensson, Erik K; Nygård, Jesper; Dick, Kimberly A; Bolinsson, Jessica
Abstract: Metal nanoparticles (NPs), in particular gold NPs, are often used in the fabrication process of semiconductor nanowires. Besides being able to induce the 1D crystallization of new material, it is highly beneficial if the NPs can be used to dictate the position and diameter of the final nanowire structure. To achieve well-defined NP arrays of varying diameter and pitch distances for nanowire growth, it is necessary to understand and control the effect that a pre-growth annealing process may have on the pre-defined NP arrays. Recently, it has been demonstrated that silver (Ag) may be an alternative to using gold (Au) NPs as seed for particle-seeded nanowire fabrication. This work brings light onto the effect of annealing of Au, Ag and Au–Ag alloy metal NP arrays in two commonly used epitaxial systems, the molecular beam epitaxy (MBE) and the metalorganic vapor phase epitaxy (MOVPE). The metal NP arrays are fabricated with the aid of electron beam lithography on GaAs 100 and 111B wafers and the evolution of the NPs with respect to shape, size and position on the surfaces is studied after annealing using scanning electron microscopy. We find that while the Au NP arrays are found to be stable when annealed up to 600 °C in a MOVPE system, a diameter and pitch dependent splitting of the particles is seen for annealing in a MBE system. The Ag NP arrays are found to be less stable, with smaller diameters (≤50 nm) dissolving during the annealing process in both epitaxial systems. In general, the mobility of the NPs is observed to differ between the two the GaAs 100 and 111B surfaces. Finally, our observations on the effect of annealing on Au–Ag alloy NP arrays suggest that these NP can withstand necessary annealing conditions for a complete de-oxidation of GaAs surfaces in both MOVPE and MBE.